XRD, SEM studies and electrical properties of metal complexes, including sodium oxalate ligand (Na2C2O4) - Aydogdu, Y; Yakuphanoğlu, Fahrettin; Aydogdu, A; Sekerci, M; Alkan, C; Aksoy, I (Elsevier Science Bv, 2002)
The crystal structure, microstructure, and electrical properties of inorganic semiconductors were based on metal complexes, including sodium oxalate ligand. The crystal structure of samples at room temperature was examined using X-ray diffraction (XRD). X-ray diffraction showed that the three samples have different crystal structures. The microstructures of the samples have also been investigated by scanning electron microscopy (SEM). These samples have been found to be inorganic semiconductors having moderate conductivities and activation energies. Room temperature conductivities of O-Co, O-Ni, and O-Cu. samples were 6.43 x 10(-9), 3.85 x 10(-7), and 2.10 x 10(-6) S/cm, respectively. The mobility and concentration of the carriers were calculated by means of current-voltage curve samples in the space charge limited region (SCLC). (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: transition metal complexes, including sodium oxalate ligands; semiconductor; activation energy